Indole metabolism and its role in diabetic macrovascular and microvascular complications - W. Hu; C. Garrison; R. Prasad; M.E. Boulton; M.B. Grant (American Heart Journal Plus)
Tryptophan (Trp), an essential amino acid obtained through dietary sources, plays a crucial role in various physiological processes. The metabolism of Trp branches into three principal pathways: the serotonin pathway, the kynurenine pathway, and the indole pathway. The kynurenine and serotonin pathways are host pathways while the indole pathway is solely the result of bacterial metabolism. Trp metabolites extend their influence beyond protein biosynthesis to affect a spectrum of pathophysiological mechanisms including, but not limited to, neuronal function, immune modulation, inflammatory responses, oxidative stress regulation, and maintenance of intestinal health. This review focuses on indole derivatives and their impact on vascular health. Trp-containing dipeptides are highlighted as a targeted nutraceutical approach to modulate Trp metabolism, enhance beneficial metabolite production, and mitigate risk factors for vascular diseases. The importance of optimizing Trp intake and dietary strategies to harness the benefits of Trp-derived metabolites for vascular health is underscored, bringing to light the need for further research to refine these therapeutic approaches.